Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd007291.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal dilator therapy for women receiving pelvic radiotherapy

Abstract: Routine dilation during or soon after cancer treatment may be harmful. There is no reliable evidence to show that routine regular vaginal dilation during or after radiotherapy prevents the late effects of radiotherapy or improves quality of life. Gentle vaginal exploration might separate the vaginal walls before they can stick together and some women may benefit from dilation therapy once inflammation has settled but there are no good comparative supporting data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 48 publications
0
43
1
1
Order By: Relevance
“…However, the specific sexual impact of this situation is variable according to the patient and her partner [3]. It seems especially problematic after radiation therapy and is inconsistently prevented by the use of dilators [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific sexual impact of this situation is variable according to the patient and her partner [3]. It seems especially problematic after radiation therapy and is inconsistently prevented by the use of dilators [4].…”
Section: Discussionmentioning
confidence: 99%
“…This procedure may reduce the incidence of vaginal stricture in our study. Unfortunately, Miles et al reported that no reliable evidence to suggest that routine dilatation prevented vaginal toxicity [22].…”
Section: Discussionmentioning
confidence: 99%
“…The current evidence does not support a specific psychosocial counselling intervention to improve sexual functioning and satisfaction. The evidence base for this recommendation consists of sixteen publications of moderate quality [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and four systematic reviews [14][15][16][17] . …”
Section: Overall Sexual Function and Satisfactionmentioning
confidence: 99%
“…A handful of systematic reviews have been published [12][13][14][15][16][17][18][19] , but they tend to focus on a single cancer or intervention type. No guidelines have comprehensively addressed sexual issues in people with cancer.…”
Section: Introductionmentioning
confidence: 99%